Management and follow-up of gallbladder polyps: Joint guidelines between the European Society of Gastrointestinal and Abdominal Radiology (ESGAR), European Association for Endoscopic Surgery and other Interventional Techniques (EAES), International Society of Digestive Surgery – European Federation (EFISDS) and European Society of Gastrointestinal Endoscopy (ESGE) - Wiles, Rebecca; Thoeni, Ruedi F.; Barbu, Sorin Traian; Vashist, Yogesh K.; Rafaelsen, Søren Rafael; Dewhurst, Catherine; Arvanitakis, Marianna; Lahaye, Max; Soltes, Marek; Perinel, Julie; Roberts, Stuart Ashley (European radiology, 2017)
Objectives The management of incidentally detected gallbladder polyps on radiological examinations is contentious. The incidental radiological finding of a gallbladder polyp can therefore be problematic for the radiologist and the clinician who referred the patient for the radiological examination. To address this a joint guideline was created by the European Society of Gastrointestinal and Abdominal Radiology (ESGAR), European Association for Endoscopic Surgery and other Interventional Techniques (EAES), International Society of Digestive Surgery – European Federation (EFISDS) and European Society of Gastrointestinal Endoscopy (ESGE). Methods A targeted literature search was performed and consensus guidelines were created using a series of Delphi questionnaires and a seven-point Likert scale. Results A total of three Delphi rounds were performed. Consensus regarding which patients should have cholecystectomy, which patients should have ultrasound follow-up and the nature and duration of that follow-up was established. The full recommendations as well as a summary algorithm are provided. Conclusions These expert consensus recommendations can be used as guidance when a gallbladder polyp is encountered in clinical practice. Key Points • Management of gallbladder polyps is contentious • Cholecystectomy is recommended for gallbladder polyps >10 mm • Management of polyps <10 mm depends on patient and polyp characteristics • Further research is required to determine optimal management of gallbladder polyps